On the experimental study of composite dessicants for energy efficient air dehumidification - Chua, K.J.; Islam, Rafiqul (IIUM Press, 2015)
This paper presents the development and performance characterization of new composite desiccants. The main compositions for the composite desiccants include silica gel, lithium chloride, calcium chloride and bentonite. Different percentage compositions of these four components were tested to determine the optimal material composition for improving moisture removal capacity under varying inlet air temperature and humidity, and amount of moisture released under different regenerative temperature. For the first time, four-layered composite desiccants were developed and tested experimentally to determine their moisture removal capacity and moisture regeneration capacity at temperature of about 60oC under inlet air conditions similar to Singapore’s tropical climate. The performances of these composite desiccants were benchmarked with the performance of pure silica gel - the most commonly used desiccant in the market today. It was observed experimentally, that employing a four-layered composite desiccant, comprising silica-gel (SiO2), Bentonite, Lithium Chloride (LiCl), and Calcium Chloride (CaCl2), has enabled greater moisture removal capacity for varying inlet air temperature and humidity ranging from 25 to 35oC and 55 to 95% relative humidity (RH). The percentage improvements, in contrast to pure silica gel, are 14 to 22.5%, and 10 to 26.3% for varying inlet air temperature and varying inlet RH, respectively.